Mechanical Cavity Creation with Curettage and Vacuum Suction (Q-VAC) in Lytic Vertebral Body Lesions with Posterior Wall Dehiscence and Epidural Mass before Cement Augmentation - Eike I. Piechowiak; Maurizio Isalberti; Marco Pileggi; Daniela Distefano; Joshua A. Hirsch; Alessandro Cianfoni (Medicina, 2019)
Background and Objectives: We describe a novel technique for percutaneous tumor debulking and cavity creation in patients with extensive lytic lesions of the vertebral body including posterior wall dehiscence prior to vertebral augmentation (VA) procedures. The mechanical cavity is created with a combination of curettage and vacuum suction (Q-VAC). Balloon kyphoplasty and vertebral body stenting are used to treat neoplastic vertebral lesions and might reduce the rate of cement leakage, especially in presence of posterior wall dehiscence. However, these techniques could theoretically lead to increased intravertebral pressure during balloon inflation with possible mobilization of soft tissue tumor through the posterior wall, aggravation of spinal stenosis, and resultant complications. Creation of a void or cavity prior to balloon expansion and/or cement injection would potentially reduce these risks. Materials and Methods: A curette is coaxially inserted in the vertebral body via transpedicular access trocars. The intravertebral neoplastic soft tissue is fragmented by multiple rotational and translational movements. Subsequently, vacuum aspiration is applied via one of two 10 G cannulas that had been introduced directly into the fragmented lesion, while saline is passively flushed via the contralateral cannula, with lavage of the fragmented solid and fluid-necrotic tumor parts. Results: We applied the Q-VAC technique to 35 cases of thoracic and lumbar extreme osteolysis with epidural mass before vertebral body stenting (VBS) cement augmentation. We observed extravertebral cement leakage on postoperative CT in 34% of cases, but with no clinical consequences. No patients experienced periprocedural respiratory problems or new or worsening neurological deficit. Conclusion: The Q-VAC technique, combining mechanical curettage and vacuum suction, is a safe, inexpensive, and reliable method for percutaneous intravertebral tumor debulking and cavitation prior to VA. We propose the Q-VAC technique for cases with extensive neoplastic osteolysis, especially if cortical boundaries of the posterior wall are dehiscent and an epidural soft tissue mass is present.